2014
DOI: 10.1002/j.0022-0337.2014.78.12.tb05844.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Anatomy Grading: Comparison Between Conventional Visual and a Novel Digital Assessment Technique

Abstract: Conventional grading of dental students' projects in preclinical courses has mainly relied on visual evaluation by experienced instructors. The purpose of this study was to compare conventional visual grading in a dental anatomy course at one U.S. dental school to a novel digital assessment technique. A total of sixty samples comprised of two sets of faculty wax-ups (n=30), student wax-ups (n=15), and dentoform teeth of tooth #14 (n=15) were used for this study. Two additional faculty members visually graded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 11 publications
6
43
0
Order By: Relevance
“…This is relevant to other studies that evaluated the repeatability of digital evaluation with the use of the same scanner at different time points and showed excellent intra class correlation of 0.93 to 0.98. 3,4 However, excellent repeatability does not necessarily indicate valid evaluation as good samples from the visual paradigm could consistently be graded as poor samples in the digital paradigm and vice versa. Therefore, the correlation of visual and digital evaluation scores was used to examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is relevant to other studies that evaluated the repeatability of digital evaluation with the use of the same scanner at different time points and showed excellent intra class correlation of 0.93 to 0.98. 3,4 However, excellent repeatability does not necessarily indicate valid evaluation as good samples from the visual paradigm could consistently be graded as poor samples in the digital paradigm and vice versa. Therefore, the correlation of visual and digital evaluation scores was used to examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Through this new technology, students can generate a high quality 3-D virtual model of their project and receive immediate feedback on discrepancies by comparing it to the gold standard determined by the course director. 4 An ideal ratio in a dental classroom setting is to accommodate one scanner for every ten students. 3 Therefore, multiple scanners are usually used to facilitate proper teaching and learning experience for all students.…”
Section: Original Researchmentioning
confidence: 99%
“…The digital grading system had previously been found to be of great help in properly evaluating students' work 20 . In addition to providing accurate measurements, the use of digital grading has been found to reduce the workload of dental instructors 23 . To use digital grading, each typodont model needs to be digitally scanned before and after tooth preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Their study found that the digital method provided a significantly more precise and reliable assessment of students' work than the hand‐grading method. Kateeb et al and Kwon et al also reported improved inter‐and intra‐grader agreement with the use of a digital assessment over the traditional visual grading method 22, 23 . Thus, the use of a digital assessment software program appeared to reduce subjectivity and variability.…”
mentioning
confidence: 98%
“…Furthermore, formal and anecdotal reports abound that visual inspection is lawed due to a variety of human factors. 1,2 What seems irrefutable is that replicating the morphology, symmetry, and cosmetic attributes of an individual's dentition must provide the best possible function, greatest longevity, and most desirable esthetics achievable. Accordingly, dental students may appropriately be counseled to recreate nature as closely as possible when restoring the human dentition.…”
mentioning
confidence: 99%